The Use of Instagram as a Fashion Reference for Fisip UNMUL Students on the @Natasharizkynew Account - Try Desy Rahmawati; Nurliah Nurliah; Dony Kristian; Harry Isra Muhammad (Sean Institute, 2026)
This study aims to explore the use of Instagram as a fashion reference among female students of the Faculty of Social and Political Sciences (FISIP), Universitas Mulawarman, through the Instagram account @natasharizkynew. The study employed a descriptive qualitative approach using the Uses and Gratifications theory, which focuses on four audience needs: information, personal identity, social interaction, and entertainment. Informants were selected using purposive sampling, consisting of Muslim female students who actively use Instagram, follow @natasharizkynew, and have adopted fashion references from the account in their daily lives. Data were collected through observation, semi-structured interviews, and documentation, and analyzed using the interactive model of Miles and Huberman, including data collection, data reduction, data display, and conclusion drawing. The findings reveal that the Instagram account @natasharizkynew fulfills students' information needs by providing references for modest, syar'i, and fashionable Muslim clothing suitable for campus activities. The account also contributes to strengthening personal identity by increasing self-confidence and helping students develop a style that aligns with their personality and values. In terms of social interaction, the content becomes a topic of discussion and fosters connections with others who share similar interests. Furthermore, the account provides entertainment by creating positive emotional experiences, including feelings of happiness, comfort, tranquility, and relief from boredom. Therefore, Instagram as a fashion reference serves not only as a source of information but also as a medium for shaping identity, enhancing social relationships, and supporting the emotional well-being of Muslim female students in the digital era..